The Role of the World Trade Organization (WTO) on the Impact of the China-United States Trade War on International Trade - Putri, Intan Eka (Activa Yuris: Jurnal Hukum, 2024)
International trade opens up new, wider markets for domestic products. Products that were originally only limited to the domestic market will have a new market share abroad. The impact of exports and imports has a positive effect on economic growth. Other benefits that can be felt are an increase in state income, foreign exchange reserves, and capital transactions. However, international trade relations do not always go well. China and the United States have been in a trade war since 2018. The two countries used to be in harmony, but because the United States had a deficit in the trade balance, exports to China amounted to US$ 405.7 billion. The United States then issued a policy of protectionism aimed at controlling export-import activities through setting customs and export-import bans, subsidies, quotas, and tariffs. This trade war continues to this day. Even though the two countries have made a Phase I agreement, they do not show that they will make peace. The impact of the China-US trade war does not only affect the two countries. The impact of the trade war is also felt in developing countries. The increase in tariffs carried out by China and the United States resulted in the two countries being unable to enter each other's markets. Thus, the two countries are eyeing other countries as a new market share to distribute their products. Indonesia as a trading partner is the target of the two countries.